Human Herpesvirus 8 Seroprevalence, China - Na He; Xiaodan Shao; Yue Chen; Tao Zhang; Veenu Minhas; Charles Wood; Tiejun Zhang (Emerging Infectious Diseases, 2012)
To summarize the seroprevalence of human herpesvirus 8 (HHV-8) in mainland China, we conducted a systematic review and meta-analysis based on available literature. Data show that differences in HHV-8 prevalence vary considerably among different ethnic groups and geographic regions. Blood-borne transmission could be a potential route for HHV-8 infection in China.